Las políticas sociales, su financiación y su efecto en los programas de desarrollo social del Ecuador, periodo 2008-2015. - Rivera Llanos, María José (2017)
The present research allows analyzing the effect of the financing of social policies in Ecuador's social development programs over a period of eight years (2008-2015), based on relevant information such as: database, tables and illustrations and on All of scientific articles related to each of the variables focused on the education, health and housing sectors; Therefore, it demonstrates the fundamental axis of the investigation of the following way: Chapter I. - Reference frame is one that details the problems that originate the investigation, the formulation of the problem, the general and specific objectives, the justification and importance of the present investigation. Chapter II.- Theoretical framework allows to explain the antecedents next to the origin and especially the theory of the variables that is investigated as it is: the financing of the social policies and their effect in the programs of social development of Ecuador (NBI). Chapter III.- Methodological framework generalizes the methodology used in the present research, as well as the analysis through the elaboration of the econometric model of multiple linear regression, elaborated in the SPSS in order to know the effect of the independent variable on the dependent variable. Chapter IV.- Conclusions and recommendations allow to deduce the culmination of the present investigation and the contributions, and at the same time to improve the processes and distribution of the researched variables. Chapter V.- Bibliography, generalizing the bibliographic material used in the present investigation. Key words.- Financing of social policies, social program, literacy, nutrition, housing.